Two species of Thoracostomopsidae (Nematoda: Enoplida) from Jeju Island, South Korea - Jeong, R.; Tchesunov, A. V.; Lee, W. (PeerJ, 2020)
During a survey of intertidal zones at beaches on Jeju Island, two species belonging to the family Thoracostomopsidae were discovered. One new species, Enoploides koreanus sp. nov. and one known species, Epacanthion hirsutum Shi & Xu, 2016 are reported. Along with morphological analysis, mitochondrial cytochrome oxidase c subunit 1 (mtCOI) sequences and 18S rRNA sequences of the species were also obtained and used to check relative p-distance and phylogenetic positions. While most species of Enoploides have long spicules, the new species belongs to a group of Enoploides with short spicules < 150 mm). Of the seven species with short spicules, the new species is most closely related to E. disparilis Sergeeva, 1974. They both have similar body length, fairly similar sized and shaped spicules with small gubernaculum running parallel to distal end of spicule, and an index value of b. The new species can be distinguished from E. disparilis by having pre-anal supplementary organ with short conical tail, while E. disparilis lacks pre-anal supplementary organ and has a long conico-cylindrical tail. Along with the description of the new species, the genus Enoploides Ssaweljev, 1912 is bibliographically reviewed and revised. Of 45 species described to date, 27 are now considered valid, 16 species inquirendae due to inadequate descriptions and ambiguity of the material examined, along with two cases of nomen nudum. With this review, we provide an updated diagnosis and list of valid species, a tabular key comparing diagnostic characters of all valid species, and a new complete key to species. One known species, Epacanthion hirsutum Shi & Xu, 2016, is reported in Korea for the first time. The morphology agrees well with the original description provided by Shi & Xu, 2016.As they had already reviewed the genus at the time of reporting four Epacanthion species, we provide only a description, depiction, and measurements for comparison purposes.